Liquid security: Managing the market for crime control - Zedner, L (2006)
Liquid security captures the shift from the solid-state technology of the criminal justice state to the more fluid, transient and dispersed operations of the private security industry. Despite its promise to sell security, the industry is often better known for the dangers it poses to the safety of people and property. Marked by high levels of corruption, violence, rapid staff turnover and high customer churn the private security industry cannot maintain consumer confidence or public respect. This article examines various attempts to manage the market for crime control and seeks to disclose their underlying rationale. Attempts to govern through industry self-regulation, market competition and the design and architecture of provision have failed to secure standards. Yet formal state regulation appears directed less at compliance with articulated ethical standards, a clear conception of what security is for and whom it should serve, than ensuring the health of the market. The state presents itself as facilitator, but appears as pimp, to the security industry. Regulation is sold as a 'business opportunity' and compliance as the means to ensuring profitability. In the telling words of the Security Industry Authority, 'Good security is good for the whole business environment'. © 2006 SAGE Publications.